ANALISIS KARAKTER VEGETATIF DAN SITOLOGI PADA BEBERAPA PLASMA NUTFAH PISANG (MUSA SP.) - Okti Hanayanti; Rr. Mustika Pramudya A. (Jurnal Ilmiah Media Agrosains, 2014)
Studies on characters of plants are required to indentification and collect the germ plasm. In the present study four banana germ plasm accessions gebyar, rajanangka, mas kirana and rajalawe were examined. The objective was to charachterize the vegetative character and to reveal the ploidy based cytology character (chromosome numbers and stomata anatomy). Some vegetative character can be specialized as a phenotypic marker of banana. Especially in Gebyar accession where the leaves have a purplish red spots and red veins. Petiole canal leaf and blotches at the petiole base is also a reference for the determination of the genome. Straight petiole canal leaf and sparse blotching showed that Gebyar tend to M.balbisiana (B genome). While open petiole canal and large blotches tend to M. acuminata (A genome) as shown in mas kirana. Rajanangka and rajalawe have open petiole canal and sparse blotching so it is possible both are the result of M.acuminata and M.balbisiana crossing namely M. paradisiaca (AB Genome). Chromosome analysis revealed different ploidies: diploid and triploid, with chromosome number 2n=22 for mas kirana, and 2n=33 for gebyar, raja nangka and rajalawe. Accession with triploidy had bigger stomatas. The stomatas were located on the upper and lower surfaces of leaves.